Suntik Mati (Euthanasia) dalam Perspektif Kesehatan dan Kitab Undang-Undang Hukum Pidana (KUHP) - Sartika Dewi; Lia Amaliya; Zarisnov Arafat; Muhammad Gary Gagarin Akbar (Direktorat Penelitian dan Pengabdian (DPPM) Universitas Pelita Bangsa, 2025)
The development of treatment or medical procedures is greatly utilized by humans to cure diseases and even to end a person's life or death. If a human experiences pain and there is no longer any hope for him to recover, plus several other factors that aggravate his situation, it can give rise to thoughts of ending his life. With advances in technology in the health sector, someone who can no longer stand the pain they are suffering from can ask a doctor to end their life. In medical terms, a person's request to a doctor to end their life because they can no longer stand the pain is usually called euthanasia. Lethal injection (Euthanasia) is the act of ending the life of a person who is experiencing very severe suffering (illness) and is medically incurable. This research aims to determine the regulations for lethal injection (euthanasia) from a positive health and legal perspective in Indonesia. The research method uses a normative juridical approach which is descriptive. Data sources consist of secondary data, namely primary, secondary and tertiary legal sources. The data collection method is literature study, then the data is analyzed qualitatively. Euthanasia, whether active or passive, is contrary to human rights. Doctors must not carry out any action that could take the patient's life, because the patient's health and safety is the highest law for doctors. Indonesia does not recognize the right to die as reflected in Article 461 of the Criminal Code, so a patient does not have the right to determine his death even if the request is based on the patient's sincerity